A preparation method and application of stabilizing window of perovskite precursor solution by water content
Patent Information
- Application Number
- CN202611318099.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]发明目的:本发明的第一目的是提供了一种通过水含量控制钙钛矿前驱体溶液稳定窗口的制备方法;本发明的第二目的是提供所述钙钛矿前驱体溶液的应用;解决了现有技术中钙钛矿前驱体溶液在空气环境下稳定窗口短、成膜结晶控制难、一致性差的问题
[0029] (1) The preparation method described in this invention significantly extends the stability window of the perovskite precursor solution: by introducing an appropriate amount of water, the stability window of the precursor solution in the air environment is extended from several hours to several days or even several weeks, which solves the problem of large batch-to-batch differences in the solution and difficulty in continuous production in industrialization;
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to a preparation method and application of a perovskite precursor solution stability window controlled by water content, belonging to the field of photovoltaic materials and device fabrication. Background Technology
[0002] In recent years, perovskite solar cells have demonstrated tremendous commercial application potential, thanks to their excellent photophysical properties, such as high light absorption coefficient, long carrier diffusion length, tunable bandgap, and low-cost solution processing performance, achieving a photoelectric conversion efficiency exceeding 28% in just over a decade. However, the industrialization of perovskite photovoltaic technology still faces two major bottlenecks. First, the preparation of high-quality perovskite thin films is highly sensitive to environmental humidity. Traditional preparation processes typically require strict control in an inert atmosphere (such as a nitrogen glove box) with water and oxygen content below 1 ppm. This significantly increases manufacturing costs and process complexity, limiting large-scale continuous production. Second, perovskite precursor solutions exhibit extremely poor stability in air, easily undergoing side reactions such as component precipitation, iodide ion oxidation, solvent evaporation, and organic cation decomposition. This results in a stability window (the time window during which the solution can maintain good film-forming performance) that is typically only a few hours, severely restricting its application in large-area preparation processes such as blade coating and slot coating.
[0003] In existing technologies, researchers have attempted to alleviate these problems through strategies such as additive engineering, solvent engineering, and ligand regulation. For example, introducing Lewis base additives can coordinate with lead ions and inhibit precursor degradation; using high-boiling-point solvents can delay the crystallization process. However, these methods have limited effectiveness in improving the long-term stability of precursor solutions in air, and most methods have poor universality for device structures.
[0004] It is worth noting that water is generally considered a harmful factor in perovskite preparation, and most research focuses on strict water removal. Currently, there is no systematic technical solution for utilizing water (including ambient humidity or added water) to extend the stability window of the precursor solution and achieve large-area module fabrication in an air environment. Therefore, developing a method for fabricating large-area perovskite modules that can utilize water to regulate the stability of the precursor solution and is suitable for air environments has significant academic and industrial value. Summary of the Invention
[0005] Objectives of the Invention: The first objective of this invention is to provide a method for preparing a perovskite precursor solution with controllable water content to achieve a stable window. The second objective of this invention is to provide applications of the perovskite precursor solution. This invention solves the problems of short stability window, difficulty in controlling film formation and crystallization, and poor consistency of perovskite precursor solutions in air environments in the prior art.
[0006] Technical solution: The present invention provides a method for preparing perovskite precursor solutions by controlling the water content to achieve a stable solution window, comprising the following steps:
[0007] (1) Dissolve the ABX3 type perovskite precursor in a solvent to prepare a perovskite precursor solution; (2) Introduce water by adding ultrapure water to the precursor solution in step (1) and / or by controlling the ambient humidity to regulate the stability window of the precursor solution.
[0008] Further, the method of adding ultrapure water in step (2) is as follows: add ultrapure water to the precursor solution at a volume ratio of 0.1 vol% to 10 vol% and stir evenly; the method of controlling the ambient humidity is as follows: place the precursor solution in an air atmosphere of 30% to 60% RH and let it stand for 0.5 to 24 hours to allow the solution to absorb water vapor in the environment.
[0009] Further, in the ABX3 type perovskite described in step (1), A is selected from one or more of formamidine ions, methylamine ions, cesium ions, and rubidium ions; B is lead ions; and X is selected from one or more of iodide ions, bromide ions, and chloride ions.
[0010] Further, the A-site ion originates from one or more of formamidine chloride (FACl), formamidine iodide (FAI), formamidine bromide (FABr), methylamine iodide (MAI), methylamine bromide (MABr), methylamine chloride (MACl), cesium iodide (CsI), cesium bromide (CsBr), cesium chloride (CsCl), rubidium iodide (RbI), rubidium bromide (RbBr), and rubidium chloride (RbCl); the B-site ion originates from one or more of lead iodide (PbI2), lead bromide (PbBr2), and lead chloride (PbCl2); the X ion is jointly provided by halide ions from the A-site and B-site sources, and is selected from one or more of iodide ions, bromide ions, and chloride ions.
[0011] Further, the solvent in step (1) is N,N-dimethylformamide and / or N-methylpyrrolidone.
[0012] The perovskite precursor solution prepared by the method of controlling the stability window of the perovskite precursor solution by water content as described in this invention.
[0013] The perovskite thin film of the present invention is prepared by coating the perovskite precursor solution onto a substrate and then annealing it.
[0014] Furthermore, the substrate is selected from one or more of glass, FTO conductive glass, ITO conductive glass, PEN or PET flexible substrate; the coating method is selected from one or more of spin coating, blade coating or slot coating; the annealing temperature is 100-180 ℃ and the time is 5-60 minutes.
[0015] The application of the perovskite thin film described in this invention in the preparation of perovskite solar cells or modules.
[0016] Furthermore, the perovskite solar cell or module has a formal structure or an inverse structure.
[0017] Furthermore, the device area of the perovskite solar cell or module is 0.1 cm². 2 Up to 100 cm 2 .
[0018] Preferably, the perovskite film is prepared in an air atmosphere and has a uniform and dense morphology, high crystallinity and low defect density.
[0019] The present invention also provides a perovskite solar cell or module based on the above-mentioned perovskite thin film.
[0020] Preferably, the perovskite solar cell or module is in a small-area device (effective area 0.1 cm²). 2 The photoelectric conversion efficiency exceeds 25%.
[0021] Preferably, the perovskite solar cell or module is used in large-area modules (effective area greater than 100 cm²). 2 The photoelectric conversion efficiency remains above 20%.
[0022] Preferably, after the precursor solution is introduced into water, it is sealed and stored in an air environment at room temperature, and its stability window is extended to more than 72 hours. During this period, the photoelectric conversion efficiency of the perovskite thin film prepared using the solution decreases by no more than 10% of the initial value.
[0023] Preferably, the stability window of the control precursor solution without water introduction does not exceed 12 hours under the same conditions.
[0024] The core design principle of this invention lies in utilizing the coordination ability of water molecules to improve the colloidal dispersion uniformity of the precursor solution, stabilize the equilibrium of the perovskite precursor solution, and extend the stability window of the precursor solution, making it suitable for air-based fabrication of large-area perovskite modules. Simultaneously, during crystallization, water molecules significantly reduce the transition energy barrier between the photoactive α phase and the non-photoactive δ phase, guiding the crystallization path preferentially towards α-FAPbI3 nucleation and growth. This invention overturns the traditional view of water as a harmful substance, fully utilizing the positive effects of trace amounts of water in precursor solution stabilization and crystallization.
[0025] Unlike existing technologies, the most important design concept of this invention is to transform water, which is traditionally considered harmful, into a functional additive to solve the problem that existing additives such as MACl cannot simultaneously ensure solution stability and film quality.
[0026] Existing technologies mainly rely on chemical additives, such as MACl, to regulate crystallization. Their mechanism of action is to promote the nucleation and growth of α-FAPbI3 by forming an intermediate phase, but they have inherent drawbacks: residues impair long-term stability and the precursor solution ages severely.
[0027] This invention uses water, which is generally considered harmful, as an additive. By utilizing the polarity of water molecules, the stability window of the precursor solution is controlled, and the phase transition energy barrier during crystallization is precisely regulated. After completing the crystallization regulation, the water can be completely removed by an annealing process, leaving no residue in the film, which is beneficial to the long-term stability of the device.
[0028] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0029] (1) The preparation method described in this invention significantly extends the stability window of the perovskite precursor solution: by introducing an appropriate amount of water, the stability window of the precursor solution in the air environment is extended from several hours to several days or even several weeks, which solves the problem of large batch-to-batch differences in the solution and difficulty in continuous production in industrialization;
[0030] (2) The perovskite precursor solution preparation method of the present invention is suitable for large-area preparation in an air environment: the method reduces the sensitivity of perovskite preparation to environmental humidity, and can achieve the preparation of high-quality thin films without strict control of inert atmosphere, which greatly reduces equipment cost and process threshold, and is especially suitable for large-area scraping or slot coating processes.
[0031] (3) The perovskite precursor solution preparation method of the present invention has strong versatility: the water control strategy is not only applicable to air atmosphere, but also applicable to inert gas or low humidity environment, and is compatible with various perovskite components such as formal and trans device structures;
[0032] (4) Process control: Controlling the transition energy barrier between the photoactive α phase and the non-photoactive δ phase during crystallization to guide the crystallization path to preferentially nucleate and grow towards α-FAPbI3;
[0033] (5) Excellent performance of perovskite thin films: The perovskite thin films prepared by this method have high crystal quality and low defect density, with efficiency of small-area devices exceeding 25% and efficiency of large-area modules >20%, and exhibit excellent long-term stability.
[0034] (6) No residue: Avoids the problem of device degradation caused by the presence of residues in the thin film due to the introduction of other additives in the existing technology.
[0035] (7) Simple process and low cost: No complex additives or expensive equipment are required. The effect can be achieved simply through passive absorption of water or trace addition, which is easy to promote in the industry. Attached Figure Description
[0036] Figure 1 The image shows the XRD pattern of a perovskite thin film prepared based on an aqueous perovskite precursor solution.
[0037] Figure 2 The DLS images are shown before and after the aqueous perovskite precursor solution was left to stand in air for 12 h.
[0038] Figure 3 The DLS images are based on anhydrous perovskite precursor solutions before and after being air-treated for 12 h.
[0039] Figure 4 To compare the UV-vis images of perovskite films prepared with and without aqueous perovskite precursor solutions;
[0040] Figure 5 PL images of perovskite films prepared with and without aqueous perovskite precursor solutions were used for comparison.
[0041] Figure 6 The efficiency decay graphs are shown for perovskite devices prepared based on aqueous perovskite precursor solutions and MACl-containing perovskite precursor solutions that have been left to stand in air for different times. Detailed Implementation
[0042] The technical solution of the present invention will be further described below with reference to the accompanying drawings.
[0043] The present invention will be described in detail below with reference to specific embodiments. It should be understood that the specific embodiments described herein are only for explaining the present invention and are not intended to limit the present invention. The scope of protection of the present invention shall be determined by the appended claims. Unless otherwise specified, the raw materials used in the following embodiments and comparative examples are all conventional commercial products in the art, and the processing techniques used are all conventional techniques in the art.
[0044] The main sources of the raw materials used in the following examples are as follows:
[0045] Formamidinium iodide (FAI, 99.5%), lead iodide (PbI2, 99.99%), methylammonium chloride (MACl), and fullerene (C 60[2-(9H-carbazole-9-yl)ethyl]phosphonic acid (2PACz) was purchased from Xi'an Yu Riguang Energy; dimethylformamide (DMF) and N-methylpyrrolidone (NMP) were purchased from Alfa Aesar; FTO conductive glass was purchased from Suzhou Shangyang Technology Co., Ltd., model A22-85; NiO X The target material was purchased from Zhongnuo New Materials Technology Co., Ltd., with the product number Ni31313; all materials were used directly without further purification.
[0046] Example 1: Actively adding ultrapure water to regulate the stability window of the precursor solution (spin coating method, small-area inverted device)
[0047] 1.1 Substrate Cleaning and Pretreatment
[0048] FTO conductive glass was selected as the substrate. The FTO glass was subjected to the following cleaning steps in sequence: ultrasonic cleaning with detergent solution for 15 minutes to remove surface grease and particulate contaminants; ultrasonic cleaning with ultrapure water for 15 minutes, repeated twice; ultrasonic cleaning with anhydrous ethanol for 15 minutes to remove organic residues; drying the substrate surface with high-purity nitrogen gas; and ultraviolet-ozone treatment for 20 minutes to remove residual organic contaminants and improve surface wettability, resulting in clean FTO glass.
[0049] 1.2 Preparation of Hole Transport Layer (NiOx)
[0050] On the FTO conductive glass treated in step 1.1, a NiOx hole transport layer was prepared by radio frequency magnetron sputtering: using a NiOx target as the sputtering source, it was deposited in an Ar atmosphere with a sputtering power of 100 W and a deposition time of 10 min, resulting in a NiOx film with a thickness of about 5–10 nm, denoted as FTO / NiOx.
[0051] 1.3 Preparation of Self-Assembled Monolayers (SAMs)
[0052] Weigh 2 mg of [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz) powder and dissolve it in 4 mL of anhydrous ethanol. Stir for 1 hour until completely dissolved to obtain a 0.5 mg / mL SAM solution. Spin-coat the SAM solution onto the FTO / NiOx surface obtained in step 1.2 at 3000 rpm for 30 seconds. Then transfer the substrate to a 100°C heating stage for annealing for 10 minutes to allow SAM molecules to bond with NiO through the phosphonic acid groups. XChemical bonds form on the surface, and self-assembly leads to a dense monolayer. Unused SAM solution during spin-coating can be recycled. The introduction of the SAM layer effectively reduces the interfacial energy barrier between NiOx and perovskite, improves hole extraction efficiency, and yields an FTO / NiOx / SAM substrate, providing a favorable nucleation template for perovskite growth.
[0053] 1.4 Preparation of precursor solution
[0054] FAI (formamidinium iodide) and PbI2 (lead iodide) were mixed in a 1:1 molar ratio to prepare a perovskite precursor solution of FAPbI3. This mixture was then dissolved in a DMF / NMP mixed solvent (8:2 volume ratio) to prepare a 1.5 mol / L perovskite precursor solution. The solution was stirred at room temperature for 2 hours until completely dissolved, yielding an orange-yellow transparent precursor solution.
[0055] 1.5 Water addition and regulation treatment
[0056] Add ultrapure water to the precursor solution at a volume ratio of 1 vol%, using a pipette for precise measurement. Stir for 1 hour in air (relative humidity 45%±5%, temperature 25±2℃) to allow the water to fully disperse and coordinate with the precursor components, obtaining a stabilized precursor solution. The solution color remains orange-yellow without significant change.
[0057] 1.6 Observation and Characterization of Stable Window
[0058] The precursor solution was sealed in a capped glass bottle and stored in an air environment (relative humidity 45%±5%, room temperature 25±2℃), and the solution status was observed periodically.
[0059] The solution, after water treatment, remained clear and transparent orange-yellow after 72 hours, with no visible precipitate. The size of the colloidal particles in the solution was characterized using dynamic light scattering (DLS) technology. A 0.5 mL sample was diluted 10-fold and measured at 25 °C; each sample was tested three times, and the average value was taken. Figure 2 The results show that the average particle size of the colloidal particles decreased after air settling. This indicates that the introduction of an appropriate amount of water disrupted the excessively strong Pb–NMP coordination bonds, promoting the dispersion of the precursor components into smaller, more uniform colloidal particles, thereby inhibiting aggregation and precipitation.
[0060] 1.7 Perovskite Thin Film Preparation
[0061] The stabilized precursor solution obtained in step 1.5 was used for perovskite film preparation. On the FTO / NiOx / SAM substrate obtained in step 1.3, 70 μL of the precursor solution was dropped onto the center of the substrate, and a two-step spin-coating procedure was used: spin-coating at 1000 rpm for 10 seconds to ensure uniform spread of the solution; and spin-coating at 5000 rpm for 20 seconds to accelerate solvent evaporation and promote film formation. After spin-coating, the spin-coated substrate was immediately transferred to a vacuum chamber, and a vacuum was quickly drawn to a pressure ≤10 Pa, maintained for 5–10 seconds, to rapidly remove residual solvent by vacuum flash evaporation, inducing rapid supersaturation and nucleation of the perovskite mesophase. After flash evaporation, the substrate was immediately transferred to a 100 °C heating stage for annealing for 1 hour. During annealing, the perovskite transformed from the mesophase to the black α-phase, yielding a high-quality perovskite film.
[0062] 1.8 Electron Transport Layer (C 60 / SnO2) preparation
[0063] (1) C 60 Layer preparation: The perovskite thin film substrate prepared in section 1.7 was transferred to a vacuum evaporation chamber and evacuated to a pressure ≤ 5 × 10⁻⁶. -4 Pa. C was deposited using a thermal evaporation method. 60 Electron transport layer, evaporation rate 0.3–0.5 Å / s. C 60 The layer thickness was 20 nm, resulting in FTO / NiOx / SAM / perovskite / C 60 .
[0064] (2) SnO2 layer preparation (atomic layer deposition ALD): In this embodiment, the FTO / NiOx / SAM / perovskite / C obtained in step (1) is prepared by ALD. 60 To achieve higher density and uniformity, a SnO2 layer was prepared. The ALD process parameters were as follows: tetratetra(dimethylamino)tin (TDMASn) was used as the tin precursor source, ultrapure water as the oxygen source, and the deposition temperature was 100°C. One deposition cycle consisted of: a TDMASn pulse of 0.1 sec → N2 purging for 20 sec → an H2O pulse of 0.1 sec → N2 purging for 20 sec. The number of cycles was 100–200, yielding a SnO2 layer with a thickness of approximately 10–20 nm, resulting in an FTO / NiOx / SAM / perovskite / C layer. 60 / SnO2. The C 60 The SnO2 double electron transport layer structure can effectively promote electron extraction, block holes, and protect the perovskite layer from damage during subsequent electrode deposition processes.
[0065] 1.9 Electrode Evaporation
[0066] Finally, the FTO / NiOx / SAM / perovskite / C obtained at 1.8 60 / Silver (Ag) electrodes are deposited on the SnO2 surface. The substrate is placed in a vacuum deposition chamber and evacuated to a pressure ≤5×10⁻ 4 Pa. The Ag electrode was deposited using thermal evaporation at a rate of 0.5–1.0 Å / s. After deposition, the Ag electrode thickness was approximately 100 nm. The effective area of this inverted perovskite solar cell was limited to 0.1 cm² by the mask. 2 .
[0067] Example 2: Passive absorption of environmental moisture to regulate the stability window of precursor solution (scalpel coating method, large-area inverted component)
[0068] 2.1 Substrate Cleaning
[0069] FTO conductive glass (10 cm × 10 cm) was selected as the substrate. The substrate cleaning and pretreatment steps were the same as in Example 1, except that the ultrasonic cleaning time was extended to 20 minutes to ensure the cleanliness of the large-area substrate.
[0070] 2.2 Hole transport layer (NiOx) and SAM fabrication (large area)
[0071] NiOx preparation: The same magnetron sputtering method as in Section 1.3 of Example 1 was used. SAM preparation: A 2 mg / mL MeO-2PACz ethanol solution was prepared, and spin-coated at 2000 rpm for 45 seconds to cover a large area of the substrate. The substrate was then annealed at 100°C for 10 minutes.
[0072] 2.3 Preparation of precursor solution and passive water absorption treatment
[0073] A 1.5 mol / L perovskite precursor solution was prepared using the same precursor components and solvent as in Section 1.4 of Example 1, but without actively adding water. The precursor solution was placed in low-humidity air (temperature 25±2℃, relative humidity 45%±5%) and stirred openly for 12 hours to allow the solution to naturally absorb moisture from the environment.
[0074] 2.4 Preparation of large-area perovskite thin films (scalpel coating method)
[0075] The precursor solution after passive water absorption treatment was used to prepare large-area perovskite films by blade coating. The blade coating process parameters were as follows: approximately 2 mL of the precursor solution was uniformly coated onto the starting end of an FTO / NiOx / SAM substrate using a pipette. An automatic blade coater was used, with the blade-to-substrate distance set to 200 μm, the coating speed to 10 mm / s, and the substrate temperature controlled at 25±2℃. After coating, the large-area substrate was transferred to a vacuum chamber, and a vacuum was quickly evacuated to a pressure ≤50 Pa (the ultimate vacuum level can be appropriately relaxed due to the large volume of the large-area chamber), maintained for 10–15 seconds, and residual solvent was rapidly removed by vacuum flash evaporation. Subsequently, the wet film was transferred to a 100℃ heating stage for annealing for 30 minutes. After annealing, a large-area perovskite film with dimensions of 10 cm × 10 cm was obtained.
[0076] 2.5 Electron Transport Layer (C 60 Preparation of SnO2 (large area)
[0077] (1) C 60 Layer preparation: A large-area perovskite thin film substrate was transferred to a vacuum evaporation chamber, and C was deposited using a thermal evaporation method. 60 The layer is 20 nm thick and has an evaporation rate of 0.3–0.5 Å / s.
[0078] (2) Preparation of SnO2 layer: ALD method was used for large-area C 60 SnO2 was deposited on the layer, with process parameters the same as in Section 1.9 of Example 1.
[0079] 2.6 Electrode Evaporation and Laser Scribing
[0080] The substrate was placed in a vacuum evaporation chamber, and a 120 nm Ag electrode was deposited. After evaporation, laser scribing technology was used to divide the large-area device into a module of 12 sub-cells connected in series.
[0081] Example 3: Optimization experiment of water addition (comparison of 0.5 vol%, 1 vol%, 2 vol%, and 3 vol%)
[0082] 3.1 Experimental Design
[0083] Example 3 is the same as Example 1, except that the volume ratio of ultrapure water added in step 1.5, the water addition treatment, is 0.5 vol%, 1 vol%, 2 vol%, and 3 vol%, respectively, and a control group without added water (0 vol%) is set up. Each group of solutions is sealed and stored in an air environment (RH 45%, 25°C).
[0084] 3.2 Evaluation of Stability Window
[0085] The stability window endpoint was defined as the time point at which a visible precipitate or a significant darkening of the color appeared in the perovskite precursor solution. The stability windows for each group are shown in Table 1 below:
[0086] Table 1 Stability window of perovskite precursor solution
[0087]
[0088] As shown in Table 1, the results indicate that adding water in the range of 0.5–3 vol% can effectively prolong the stability window, with the optimal water addition being 1–2 vol%.
[0089] Example 4: Monitoring Device Performance Degradation During the Stable Window
[0090] Experimental Method: The precursor solution was prepared according to step 1.4 of Example 1, and ultrapure water was added at 1 vol%. The solution was stored in air (45% ± 5% RH, 25°C). The solution was taken at 0 hours (freshly prepared), 24 hours, 48 hours, 72 hours, and 96 hours of storage, and processed according to the process in Example 1 (FTO / NiOx / SAM / perovskite / C 60 Inverted devices were fabricated using a mixture of SnO2 and Ag. Six parallel devices were fabricated at each time point, and the average efficiency was taken.
[0091] Comparative Example 1 (prepared directly in air without adding water)
[0092] Comparative Example 1 is the same as Example 1, except that ultrapure water is not added in step 1.5.
[0093] Compared to Example 1, in terms of observing and characterizing the stability window of the precursor solution, Comparative Example 1 showed visible fine yellow precipitates after standing in air for 12 hours. Figure 3 The increase in the average particle size of the colloidal particles indicates that component degradation has occurred. Figure 1 The results from the Control group show that the (100) crystal plane of the perovskite thin film prepared in step 1.7 of Comparative Example 1 is significantly lower than that of Example 1. Furthermore, the average efficiency of the assembled device is 17.8%, far lower than that of Example 1. This comparative example illustrates that it is difficult to prepare high-quality thin films in an air environment using conventional precursor solutions without water conditioning.
[0094] Comparative Example 2 (excess water added, 10 vol%)
[0095] Comparative Example 2 was identical to Example 1, except that 10 vol% of ultrapure water was added in step 1.5. After stirring for 2 hours, localized flocculent precipitates appeared in the precursor solution. This solution was spin-coated into a film and a device was assembled. Numerous pores appeared on the substrate. The average device efficiency was 19.2%, with very poor repeatability. This comparative example illustrates that the amount of water introduced must be controlled within an appropriate range; excessive water will disrupt the colloidal balance of the precursor solution.
[0096] Comparative Example 3 (prepared in an inert atmosphere, without the addition of water)
[0097] Comparative Example 3 is the same as Example 1, except that steps 1.4 to 1.7 are carried out in a nitrogen glove box (water < 0.1 ppm, oxygen < 0.1 ppm).
[0098] The device fabricated in Comparative Example 3 had an average efficiency of 22.4%. However, when the precursor solution was transferred to an air environment (45% RH) for storage, it became unusable for perovskite solar cell fabrication after 12 hours. This comparative example illustrates that although high-efficiency perovskite solar cells can be fabricated in an inert atmosphere, the precursor solution rapidly degrades upon exposure to air; while the present invention, through the control of water, endows the precursor solution with long-term stability and process tolerance in an air environment.
[0099] Comparative Example 4 (using other additives instead of water)
[0100] Comparative Example 4 is the same as Example 1, except that in step 1.5, an equal amount of methylammonium chloride (MACl) is used instead of ultrapure water.
[0101] The results showed that the stability window of the precursor solution after the addition of MACl was 6 hours, which was much shorter than the 72 hours after water treatment in Example 1. The efficiency degradation was as follows: Figure 6 As shown, the precursor solution containing MACl exhibits severe degradation, while the degradation of the aqueous precursor solution is significantly slowed. These results indicate that water has a unique effect on extending the stability window of the precursor solution, and cannot be replaced by simple solvent dilution or polarity adjustment.
[0102] Experimental Example 1: Characterization of Thin Film Morphology and Crystallinity
[0103] The crystal structures of the perovskite thin films prepared in Example 1 and Comparative Example 1 were characterized using X-ray diffraction (XRD). Test conditions: scan range 5°–30°, step size 0.05°, scan speed 5° / min. Diffraction patterns are shown below. Figure 1The results show that the hydrated (Target) film exhibits characteristic diffraction peaks of the perovskite (100), (200), and (210) crystal planes at 14.1°, 28.4°, and 31.8°. Among them, the peak intensity at 14.1° is significantly higher than that of the unhydrated group in Comparative Example 1 (Control), while the peak intensities of PbI2 (12.7°) and δ phase (11.7°) impurity phases are significantly reduced, indicating that the hydrated treatment promotes the preferred orientation growth of perovskite and inhibits the formation of impurity phases such as PbI2.
[0104] The image was characterized using ultraviolet-visible (UV-vis) absorption spectroscopy. Figure 4 The results show that, within the wavelength range of 500–900 nm, the absorbance of the perovskite film prepared in step 1.7 of Example 1 is significantly higher than that of the perovskite film prepared in step 1.7 of Comparative Example 1. This indicates that the perovskite film prepared by the present invention has higher α-phase purity and better crystal quality, improved film density, and effectively enhanced light-harvesting ability.
[0105] The quality of perovskite thin films was characterized by photoluminescence (PL) testing. Figure 5 The results show that, compared to the film prepared in Comparative Example 1, the PL intensity of Example 1 is enhanced and slightly blue-shifted, demonstrating that the film defects are effectively passivated and non-radiative recombination is suppressed, indicating that the present invention improves the crystallinity quality of the film.
[0106] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing perovskite precursor solutions with controlled water content, characterized in that, Includes the following steps: (1) Dissolve the ABX3 type perovskite precursor in a solvent to prepare a perovskite precursor solution; (2) Water is introduced by adding ultrapure water to the precursor solution in step (1) and / or by controlling the ambient humidity, thereby regulating the stability window of the precursor solution.
2. The preparation method according to claim 1, characterized in that, The method of adding ultrapure water in step (2) is as follows: add ultrapure water to the precursor solution at a volume ratio of 0.1 vol% to 10 vol% and stir evenly; the method of controlling the ambient humidity is as follows: place the precursor solution in an air atmosphere of 30% to 60% RH and let it stand for 0.5 to 24 hours to allow the solution to absorb water vapor in the environment.
3. The preparation method according to claim 1, characterized in that, In step (1), in the ABX3 type perovskite, A is selected from one or more of formamidine ions, methylamine ions, cesium ions, and rubidium ions; B is lead ions; and X is selected from one or more of iodide ions, bromide ions, and chloride ions.
4. The preparation method according to claim 1, characterized in that, The solvent mentioned in step (1) is N,N-dimethylformamide and / or N-methylpyrrolidone.
5. A perovskite precursor solution prepared by the preparation method of claim 1.
6. A perovskite thin film prepared based on the perovskite precursor solution according to claim 5, characterized in that, It is prepared by coating the perovskite precursor solution onto a substrate and then annealing it.
7. The perovskite thin film according to claim 6, characterized in that, The substrate is selected from one or more of glass, FTO conductive glass, ITO conductive glass, PEN or PET flexible substrate; the coating method is selected from one or more of spin coating, blade coating or slot coating; the annealing temperature is 100-180 ℃ and the time is 5-60 minutes.
8. The use of the perovskite thin film according to any one of claims 6 to 7 in the preparation of perovskite solar cells or modules.
9. The application according to claim 8, characterized in that, The perovskite solar cell or module has a formal or inverted structure.
10. The application according to claim 8, characterized in that, The device area of the perovskite solar cell or module is 0.1 cm². 2 Up to 100 cm 2 .